High shares of senior researchers aged over 50 - Beintema, Nienke M. (International Food Policy Research Institute, 2020)
This year marks the 20th anniversary of the inception of ASTI. During this time, governments, donors, and international organizations have used ASTI’s evidence to guide agricultural research investment and policy decisions, to assess areas of underinvestment, to identify capacity gaps and training needs, and to demonstrate the returns to agricultural research investment. This series of notes marks this important milestone by focusing on—and updating—some of the key advancements and insights ASTI data have enabled in the past 20 years. This note focuses on the challenge in many countries, particularly in Africa south of the Sahara (SSA), of disproportionate shares of PhD-qualified researchers in their 50s and 60s.